Advances in IVUS/OCT and Future Clinical Perspective of Novel Hybrid Catheter System in Coronary Imaging - Ono, Masafumi; Kawashima, Hideyuki; Hara, Hironori; Gao, Chao; Wang, Rutao; Kogame, Norihiro; Takahashi, Kuniaki; Chichareon, Ply; Modolo, Rodrigo; Tomaniak, Mariusz; Wykrzykowska, Joanna J.; Piek, Jan J.; et al. (Frontiers in Cardiovascular Medicine, 2020)
Intravascular ultrasound (IVUS) and optical coherence tomography (OCT) have been developed and improved as both diagnostic and guidance tools for interventional procedures over the past three decades. IVUS has a resolution of 100 µm with a high tissue penetration and capability of assessing the entire structure of a coronary artery including the external elastic membrane, whereas OCT has a higher resolution of 10-20 µm to assess endoluminal structures with a limited tissue penetration compared to IVUS. Recently, two companies, CONAVI and TERUMO, integrated IVUS and OCT into a single catheter system. With their inherent strength and limitations, the combined IVUS and OCT probes are complementary and work synergistically to enable a comprehensive depiction of coronary artery. In this review we summarize the performance of the two intracoronary imaging modalities - IVUS and OCT, and discuss the expected potential of the novel hybrid IVUS-OCT catheter system in the clinical field.